What can the Thinking and Working Politically community learn from peace and conflict mediation? - Douglas, Alex (From Poverty to Power, 2018)
Wily aid practitioners have long understood the importance of adapting their programs to the political environment, and even use their activities to push politics in a progressive direction. But this magic was spun secretly, hidden behind logframes and results frameworks. Only recently has a range of programs been permitted to escape the dead hand of technocracy. But there was one corner of the development and humanitarian world that never needed to shroud its political ambitions; those of us working on resolving violent conflicts. Donors have always understood our work could never be disembodied from politics. This field included elements of the UN, regional organisations, and NGOs, such as the one I work for: the Centre for Humanitarian Dialogue. With a new focus on development being enabled by a series of ‘deals’ between different actors, it seems timely to examine the strategies used to reach peace agreements and whether they contain broader lessons for TWP/DDD/Adaptive Management.

Thinking and working politically in Somalia: A case study on the Somalia Stability Fund - Laws, Ed (TWP Coommunity of Practice and ODI, 2018)

Thinking and Working Politically through Applied Political Economy Analysis. A guide for practitioners - Rocha Menocal, Alina; Cassidy, Marc; Swift, Sarah; Jacobstein, David; Rothblum, Corinne; Tservil, Ilona (USAID, 2018)
Thinking and Working Politically (TWP) through Applied Political Economy Analysis (PEA). A guide for practitioners Have you ever done everything right in a development program — followed every technical best practice — but still missed the mark? When this happens, it often relates to factors in the context beyond any external development actor’s ability to control.

Thinking and working politically: An introduction to key ideas, examples and further reading - Laws, Ed; Marquette, Heather (TWP Community of Practice, 2018)

Thinking and working politically: Reviewing the evidence on the integration of politics into development practice over the past decade - Laws, Ed; Marquette, Heather (TWP Community of Practice, 2018)